2021
DOI: 10.3389/fnbeh.2021.795030
|View full text |Cite
|
Sign up to set email alerts
|

Linking Ethanol-Addictive Behaviors With Brain Catecholamines: Release Pattern Matters

Abstract: Using a variety of animal models that simulate key features of the alcohol use disorder (AUD), remarkable progress has been made in identifying neurochemical targets that may contribute to the development of alcohol addiction. In this search, the dopamine (DA) and norepinephrine (NE) systems have been long thought to play a leading role in comparison with other brain systems. However, just recent development and application of optogenetic approaches into the alcohol research field provided opportunity to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 155 publications
0
6
0
Order By: Relevance
“…Using FSCV recordings coupled with the selective optogenetic activation of dopamine VTA-nucleus accumbens circuitry, it was confirmed that high and low frequencies may generate phasic and tonic increases in dopamine release, respectively [46,47], which were previously detected in behaving animals [11][12][13]48]. This allowed Budygin's group to explore the relationship between dopamine transmission patterns and alcohol self-administration [49]. It has been revealed that phasic pattern of accumbal dopamine transmission within mesolimbic circuitry enhanced alcohol seeking, whereas tonic pattern inhibited alcohol-seeking and taking behaviors [47,50].…”
Section: Drug and Alcohol Addictionsmentioning
confidence: 67%
“…Using FSCV recordings coupled with the selective optogenetic activation of dopamine VTA-nucleus accumbens circuitry, it was confirmed that high and low frequencies may generate phasic and tonic increases in dopamine release, respectively [46,47], which were previously detected in behaving animals [11][12][13]48]. This allowed Budygin's group to explore the relationship between dopamine transmission patterns and alcohol self-administration [49]. It has been revealed that phasic pattern of accumbal dopamine transmission within mesolimbic circuitry enhanced alcohol seeking, whereas tonic pattern inhibited alcohol-seeking and taking behaviors [47,50].…”
Section: Drug and Alcohol Addictionsmentioning
confidence: 67%
“…Despite extensive evidence on the dysregulation of dopaminergic, noradrenergic, and serotonergic signaling in AUD, we detected no significant changes in the concentrations of NE, DA, 5-HT, HVA, and 5-HIAA in both the striatum and hippocampus of C3H and B6 mice (Fitzgerald, 2013;Marcinkiewcz et al, 2016;Haass-Koffler et al, 2018;Khom et al, 2020;Grinevich et al, 2021). Notably, B6 alcohol-exposed mice displayed higher serotonin turnover in the hippocampus, as suggested by the increased 5-HIAA/5-HT ratio, measured indirectly, suggesting an alteration of the serotoninergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported similar outcomes in mice, including hypomagnesemia, hypophosphatemia and hypokalemia in the cerebellum and whole brain homogenates (Belknap et al, 1978;Te Riele and Verrips, 2014). Dopamine (DA), norepinephrine (NE) and 5-HT can all be altered in AUD and during withdrawal, with good concordance between human and rodent studies (Marcinkiewcz et al, 2016;Haass-Koffler et al, 2018;Grinevich et al, 2021). Conversely to a hyperdopaminergic state following acute alcohol exposure, chronic alcohol exposure and withdrawal result in a hypodopaminergic state that is thought to play a significant part in the neurotransmission mechanisms regulating alcohol dependence and relapse (Koob, 2003;Melis et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Another study, including healthy participants, found that acute alcohol intake caused plasma NA to increase 30 min after consumption lasting approximately 4 h 51 . Acute alcohol significantly affects catecholamine dynamics, implying that continuous alcohol exposure might cause profound modulations in both DA and NA brain systems 52 . Animal experiments have shown that long‐term alcohol intake alters dorsal striatal dopamine release and uptake and the regulation of DA release by D2/3 dopamine autoreceptors in male but not female rhesus macaques 53 .…”
Section: The Neurobiology Of Aud In Relation To the Neurobiological A...mentioning
confidence: 99%